MARKETING STRATEGY FOR STUDENT SAVINGS PRODUCTS AT BANK SUMUT KCP SYARIAH HM JONI - Ma’arif Noer Lubis; Wahyu Syarvina; Rahmat Daim Harahap (RADJA PUBLIKA, 2025)
The Student Savings Account (Simpel) program is a government initiative supervised by the Financial Services Authority (OJK) in collaboration with banking institutions in Indonesia, aimed at promoting financial education and cultivating a saving habit from an early age. Bank Sumut KCP Syariah HM Joni, as part of a growing Islamic bank, offers a student savings product based on the mudharabah contract. This study aims to analyze the marketing strategies employed by Bank Sumut KCP Syariah HM Joni toward Islamic College Al-Ulum School and to identify the supporting factors and obstacles in increasing students' interest in saving. A qualitative descriptive approach was used, involving interviews with the bank's marketing officer, direct observation, and documentation of customer growth data at Al-Ulum School. The findings reveal that although marketing efforts have been made through educational approaches, students' interest in saving remains low. The main contributing factors include a lack of financial literacy and awareness among students, teachers, and parents regarding the importance of saving from an early age as a foundation for financial management skills. This study recommends enhanced and continuous financial education and outreach to address challenges effectively.